PENGARUH KEPERCAYAAN, KEMUDAHAN DAN KEAMANAN TERHADAP KEPUTUSAN PEMBELIAN PADA SITUS MARKETPLACE SHOPEE - Dahlia, Rena; Arini, Eti (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2024)
The title of this research is the influence of trust, convenience, and security on purchasing decisions on the marketplace marketplace site (study on students of the Faculty of Economics and Business, Management Study Program, University of Muhammadiyah Bengkulu). This study aims to determine the effect of trust, convenience, and security on purchasing decisions at marketplace site shoppe. This research was conducted on December 10, 2022. The sample of this research is marketplace shopee consumers among 96 students of the Faculty of Economics and Business, Management Study Program, Muhammadiyah University of Bengkulu. The sampling technique is probability sampling. The method used in this study is a quantitative method with Multiple Linear Regression analysis using SPSS 24 for windows. Based on the results of multiple linear regression, the following equation is obtained: Y = 2.256 + 0.088 (X1) + 0.372 (X2) + 0.540 (X3) The research results and hypotheses in this study indicate that trust (X1), convenience (X2), and security (X3) has a positive and significant effect both partially and simultaneously on purchasing decisions (Y) on the marketplace shopee site for Students of the Faculty of Economics and Business, Management Study Program, University of Muhammadiyah Bengkulu. Keywords: Trust, Convenience, Security, Purchase Decision